2022
DOI: 10.1186/s10194-022-01417-9
|View full text |Cite
|
Sign up to set email alerts
|

Resumption of migraine preventive treatment with CGRP(-receptor) antibodies after a 3-month drug holiday: a real-world experience

Abstract: Background Migraine frequency increases after the cessation of successful preventive treatment with CGRP(-receptor) monoclonal antibodies (mAbs). In this study, we aimed to evaluate the course of migraine after treatment resumption. Methods Patients with migraine, who started treatment with the same CGRP(-R) mAb after a three-month drug holiday were included in this analysis. We collected headache data at four prospective visits: 1) during the four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 29 publications
2
36
0
5
Order By: Relevance
“…CGRP/(R)-AKs: Erenumab, Galcanezumab, Fremanezumab Eptinezumab Zusammenfassend zeigen die bisherigen Daten (10 Studien, 2171 Patienten), dass nach Absetzen einer erfolgreichen Migräneprophylaxe mit CGRP/(R)-AK bei der Mehrzahl der Patienten wieder eine schrittweise Zunahme der Migränefrequenz, der migränebedingten Alltagseinschränkungen und eine Zunahme des Bedarfs an Akutmedikation eintritt [30][31][32][33][34][35][36][37][38][39]. Die Studien variieren in der Methodik (retrospektiv versus prospektiv, kontrolliert versus "realworld"-Daten, Fallzahlen, Therapie-und Nachbeobachtungszeiträume, chronische versus episodische Migräne, mit versus ohne Medikamentenübergebrauch, untersuchte Wirkstoffe), was die Aussagekraft direkter Vergleiche einschränkt.…”
Section: Spezifische Prophylaxemedikamenteunclassified
See 1 more Smart Citation
“…CGRP/(R)-AKs: Erenumab, Galcanezumab, Fremanezumab Eptinezumab Zusammenfassend zeigen die bisherigen Daten (10 Studien, 2171 Patienten), dass nach Absetzen einer erfolgreichen Migräneprophylaxe mit CGRP/(R)-AK bei der Mehrzahl der Patienten wieder eine schrittweise Zunahme der Migränefrequenz, der migränebedingten Alltagseinschränkungen und eine Zunahme des Bedarfs an Akutmedikation eintritt [30][31][32][33][34][35][36][37][38][39]. Die Studien variieren in der Methodik (retrospektiv versus prospektiv, kontrolliert versus "realworld"-Daten, Fallzahlen, Therapie-und Nachbeobachtungszeiträume, chronische versus episodische Migräne, mit versus ohne Medikamentenübergebrauch, untersuchte Wirkstoffe), was die Aussagekraft direkter Vergleiche einschränkt.…”
Section: Spezifische Prophylaxemedikamenteunclassified
“…Hier sind Studiendaten zur gesundheitsbezogenen Lebensqualität während der Therapiepause mit CGRP/(R)-AK zu beachten, die bereits in Woche 8-16 nach Therapieende eine signifikante Zunahme der kopfschmerzbedingten Einschränkung der Alltagsaktivitäten und der Lebensqualität zeigen [37]. Ist eine Fortsetzung der Therapie mit CGRP/(R)-AK nötig, so belegen die dazu bislang publizierten Studien, dass die Mehrzahl der Patienten nach Wiederbeginn der CGRP/(R)-AK-Therapie genauso gut wie in der initialen Behandlung ansprechen [30,32,35].…”
Section: Spezifische Prophylaxemedikamenteunclassified
“…Two studies describe patients undergoing planned and unplanned treatment breaks [47,68], 9 explicitly describe a planned break in treatment with the anti-CGRP-mAb [52,62,73,80,83,84,92,95,101] and 6 reported an unplanned break in treatment [42,45,58,66,74,96]. In contrast, 46 of these 63 real-world studies did not have study periods which allowed for analysis of a treatment break or did not describe a treatment break at all.…”
Section: Treatment Breakmentioning
confidence: 99%
“…In contrast, 46 of these 63 real-world studies did not have study periods which allowed for analysis of a treatment break or did not describe a treatment break at all. Most interestingly, the studies addressing planned treatment breaks, made their primary endpoints the effect of pausation of treatment -which meant little was discussed about their treatment benefit leading up to the treatment break [52,62,73,80,83,84,92,95,101]. Eight studies reported time to migraine return and the corresponding patient number [47,52,74,80,83,84,92,101].…”
Section: Treatment Breakmentioning
confidence: 99%
See 1 more Smart Citation